Respuesta :

dyven
I just took the test, it was A. 4x^3+12x^2-5x-15 :)

Answer:

[tex](fg)(x)=4x^3+12x^2-5x-15[/tex]

First option is correct.

Step-by-step explanation:

We have been given that

[tex]f(x)=4x^2-5[/tex]

[tex]g(x)=x+3[/tex]

We know that [tex](fg)(x)=f(x)g(x)[/tex]

Hence, we have to find the product of f(x) and g(x)

[tex](fg)(x)=(4x^2-5)(x+3)[/tex]

Apply distributive property

[tex](fg)(x)=4x^2\cdot x+4x^2\cdot3-5x-5\cdot3[/tex]

Simplifying, we get

[tex](fg)(x)=4x^3+12x^2-5x-15[/tex]

First option is correct.